Pengaruh Sujud Sumarah Dalam Meningkatkan Kesalehan Sosial Masyarakat Paguyuban Sumarah di Desa Somoroto, Kauman, Ponorogo (Departement of Comparative Study of Religions, 2024)
Sumarah prostration is a sacred ritual in the sumarah community which is often considered to be occult, namely a mystical activity that involves the help of a shaman or ancestral spirits. Especially among the majority of society who believe in heavenly religions, it is difficult to justify it. Sometimes this phenomenon becomes a big topic of discussion and a big question among communities adhering to the divine religion in particular, so that the question arises as to why the prostration of sumarah is done and what the benefits and purpose of doing the prostration of sumarah are. This research focuses on fundamental questions regarding the influence of prostration sumarah itself on its adherents. The aim of this research is to understand and examine the influence of the sumarah prostration ritual so that it is considered to have an impact on the social life of the perpetrators. Descriptive analysis methods were carried out to explore research on this view, using interview techniques and participant observation. In the results found, there are two prominent effects, first, in terms of taste, the impact of prostration sumarah is improving character, being able to control attitudes that can harm other people, gaining calm and peace of mind. Second, in terms of outlook and mindset, prostration sumarah makes its adherents only judge someone based on their morals without looking at other worldly advantages.